Students' Mathematical Problem Solving Ability in View of Learning Motivation Through the MURDER Learning Model Assisted by Animation Videos - Faza, Safana Aulia; Wijayanti, Kristina (Unnes Journal of Mathematics Education, 2023)
This research was carried out with the aim of analyzing the effectiveness of the MURDER learning model assisted by animated videos on students' mathematical problem solving abilities and describing mathematical problem solving abilities in terms of student learning motivation through the MURDER learning model assisted by animated videos. This research employed a mixed-method research approach with a sequential explanatory design model. The study population consisted of students from all Class VIII of SMP Negeri 6 Semarang for the academic year 2022/2023, comprising eight classes. The research sample was class VIII G, with 32 students, and class VIII F, with 32 students. The results of this research indicate that the MURDER learning model assisted by animated videos is effective for mathematical problem solving abilities. In addition, a description of students' mathematical problem solving abilities was obtained in terms of learning motivation. Students with high learning motivation meet all indicators of mathematical problem solving abilities. Students with moderate learning motivation tend to be able to meet the indicators of mathematical problem solving ability. Students with low learning motivation tend to be unable to meet indicators of mathematical problem solving ability.